2016
DOI: 10.1109/tmtt.2016.2519342
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Physical Analysis of Thermal Degradations of AlGaN/GaN HEMT Under Radar-Type Operating Life

Abstract: Failure mechanisms in AlGaN/GaN HEMT RF power amplifiers implemented on silicon substrate and envisaging radar operating conditions are investigated in this paper. Several power amplifier prototypes have been designed, fabricated, characterized, and tested. Ageing tests were performed in conditions as close as possible to real applications. Ageing under increased drain voltage allowed studying both thermal and electrical aspects. Characterization performed before and after ageing tests proved that ageing proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In 2020, Liu et al [36] firstly reported the single pulse unclamped inductive switching (UIS) withstanding physics and failure mechanism for p-GaN HEMT. All evidence eliminates other failure mechanisms, leaving the inverse piezoelectric effect to be the predominant one.…”
Section: High Electric Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2020, Liu et al [36] firstly reported the single pulse unclamped inductive switching (UIS) withstanding physics and failure mechanism for p-GaN HEMT. All evidence eliminates other failure mechanisms, leaving the inverse piezoelectric effect to be the predominant one.…”
Section: High Electric Stressmentioning
confidence: 99%
“…In 2016, Temcamani et al [37] investigated failure mechanisms of Si-based GaN HEMT RF PAs under radar operating conditions. Characterizations performed before and after ageing tests prove that gate metal contacts are very sensitive to temperatures, and the irreversible part of the ageing process at gate region is mainly due to thermal stresses.…”
Section: High Thermal Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…AlGaN/GaN high-electron-mobility transistors (HEMTs) are now applied in high-power and high-frequency devices. [1] Nevertheless, in these applications they are subjected to high electrical, mechanical, and thermal stresses that can result in various levels of device degradation. The evidence of structural degradation of these devices due to high-power and hightemperature stresses was found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…AlGaN/GaN high‐electron‐mobility transistors (HEMTs) are now applied in high‐power and high‐frequency devices . Nevertheless, in these applications they are subjected to high electrical, mechanical, and thermal stresses that can result in various levels of device degradation.…”
Section: Introductionmentioning
confidence: 99%